2000
DOI: 10.1007/s150100070040
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Amphotericin B (AmBisome) in the Treatment of Neonatal Candidiasis in Very Low Birth Weight Infants

Abstract: AmBisome represents an effective, safe and convenient antifungal agent in the therapy of systemic fungal infections in very low birth weight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 24 publications
(28 reference statements)
0
38
0
1
Order By: Relevance
“…However, there is notably less reported renal and liver toxicity with LAMB (Table 3, Supplementary Table 2, http://links.lww.com/COID/A1). Several authors reported that patients tolerated LAMB better after being switched from DAMB [21,46,47].…”
Section: Amphotericin B Lipid Formulationsmentioning
confidence: 99%
“…However, there is notably less reported renal and liver toxicity with LAMB (Table 3, Supplementary Table 2, http://links.lww.com/COID/A1). Several authors reported that patients tolerated LAMB better after being switched from DAMB [21,46,47].…”
Section: Amphotericin B Lipid Formulationsmentioning
confidence: 99%
“…The age of onset of disseminated fungal infection among NICU patients has a wide range, with some cases occurring in the first week of life and others occurring later than 6 months of age. Among VLBW infants, the mean onset of infection ranges from 15 to 33 days of age (31,234,366,402). Fungal sepsis may occur earlier in infants with lower gestational age and birth weight.…”
Section: Vol 17 2004 Infections In Very-low-birth-weight Infants 661mentioning
confidence: 99%
“…JusterReicher el al. [13] also found no major adverse effects in 24 VLBW infants treated with AmBisome (mean GA of 26 weeks), and Weitkamp et al [14] reported the absence of nephrotoxicity related to AmBisome therapy in 21 VLBW infants (GA age 23-31 weeks). In another study of 52 preterm infants, Linder et al showed an improvement in renal function during treatment with three amphotericin B preparations.…”
Section: Discussionmentioning
confidence: 99%
“…However, ABLC may also induce azotemia, a decreased glomerular filtration rate, and severe hypokalemia [8,9]. The ABLC and other lipid formulations of amphotericin B, such liposomal amphotericin B, have been used in preterm infants, term infants, children, and adults [7,8,[10][11][12][13][14][15][16][17]. Although a number of studies have compared the different types of lipid formulations of amphotericin B or compared a lipid formulation and regular amphotericin B in infants and adults [7,9], the effect of ABLC (Abelcet) on renal function and serum electrolytes in VLBW infants has not been fully investigated.…”
Section: Introductionmentioning
confidence: 99%